A new building history of the church in the Zutphen district Nieuwstad (Bulletin KNOB, 2004)
The foundation of the parish church of Our Lady in the Zutphen district Nieuwstad (New Town), dates back to the mid-13th century and is probably due to Otto II, Count of Guelder (1229-1271). He is assumed to have been involved in the foundation of the Nieuwstad as well. Till 1312 this Nieuwstad formed a separate town and was only that year incorporated in the Zutphen Oude Stad (Old Town). The church was first mentioned in 1272.Considerable parts of the 13th century church still exist, partly invisible in the plastered walls of the nave and visible in the lower parts of the tower. At first the building must have appeared as a small chapel, consisting of only four bays: two smaller ones of the sanctuary and two wider ones of the nave. Then the impressive tower was built and finally the connecting bay between this chapel and the tower.A small part of a Rhinelandish decoration scheme recently discovered in the nave points at the collegiate church of St. Walburg in Zutphen, in the way it was renewed in the first half of the 13th century. The traceries in the tower show connections with the Broederenkerk (church of the Dominicans) in Zutphen built around 1300.No building activities are traceable in the church during the 14th century. In 1439 funds were donated by the city to enlarge the tower: some wooden parts in the present huge spire have been dendrochronologically dated to after 1441 ± 6 years. Ten years later, 1459, the altar in the new sanctuary was consecrated (roof construction: 1453/1454d). The adjoining most eastern bays of the northern and southern aisles must have been built in this period as well.Next, the southern aisle was completed between around 1472d ± 5 and 1482/1483d, 1483/1484d in two building campaigns. At the same time the extant 13th century nave was adapted to this enlargement, including new roof constructions (1460d ± 5 and 1485/1486d) replacing the original ones. In this way the building took the form of a hall church consisting of two naves. In the first decades of the 16th century (1501-1510d and 1528/1529d) the northern aisle was finished in two building campaigns as well, creating the present form of a hall church of three naves.Following the Reformation in 1591, the church was reinstated as a Protestant church until 1646. During the years 1795 to 1816 the building had a military use, as it may also have had in the period 1591-1646 as well. From 1816 onwards the church, now consecrated to St. John the Baptist, is used by the Roman Catholic population of Zutphen and underwent several restorations, of which the last was finished this year (2004).